EROSION RATE OF RESERVOIR DEPOSIT AS REVEALED BY LABORATORY EXPERIMENT - A. S. Amar (Journal of the Civil Engineering Forum, 2012)
The construction of dams and reservoirs in a river can give significant impacts on its flow of water and sediment, and can cause long-term morphological changes on the river. Reservoir sedimentation can reduce a reservoir’s effective flood control volume, and in some severe cases can cause overtopping during floods. Sediment deposition against a dam can reduce its stability, and affect the operation of low-level outlet works, gates, and valves. The abrasive action of sediment particles can roughen the surface of release facilities and can cause cavitations and vibration. Sedimentation can also affect a reservoir’s water quality, and reduce its flood control, water supply, hydropower, and recreation benefits. Consequently, taking sedimentation into consideration not only in the planning and design, but also in the operation and maintenance of a dam and reservoir is important. Keywords: Erosion rate, reservoir deposit, shear stress.